Beyond burnout: a case study that associates quiet quitting among working women at a higher education institution in Selangor - Chan, Angela Nguk Fong; Rachel Rosseline Ronald Batahong, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The rising expectation of working women, especially married women, to balance professional and family responsibilities often lead to burnout, characterised by emotional exhaustion, depersonalisation, and reduced personal accomplishment. This issue is worsened by societal expectations that women are solely responsible for household duties, even while contributing financially. Despite management awareness, burnout often remains unaddressed. Following the COVID-19 pandemic, the concept of quiet quitting where employees disengage and perform only the bare minimum has become more prevalent. This study investigates burnout and quiet quitting among female employees at a higher education institution in Selangor using a quantitative research design. A purposive sampling method was used to survey 74 working women with the Maslach Burnout Inventory (Maslach & Jackson, 1981) and the Quiet Quitting Scale (Galanis et al., 2023a). Results indicate that a majority experience high levels of emotional exhaustion and depersonalisation, along with low personal accomplishment. However, Spearman’s Rank correlation found no significant relationship between burnout and quiet quitting (r = 0.003, p-value = 0.979). These findings suggest that while burnout is common, other factors may drive quiet quitting, warranting further exploration into additional organisational and psychological influences to enhance employee well-being and retention in academia.